2014
DOI: 10.1128/jcm.01639-14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Alere i Influenza A&B Nucleic Acid Amplification Test by Use of Respiratory Specimens Collected in Viral Transport Medium

Abstract: The Alere i Influenza A&B assay is a newly developed rapid molecular assay which has the potential to generate results within 15 min from sample collection. In this study, we evaluated the Alere i Influenza A&B assay by using salvaged frozen respiratory specimens that were collected in viral transport medium from children ages 10 months to 19 years. Alere i Influenza A&B assay test results were compared with viral culture and ProFlu ؉ real-time reverse transcription-PCR (RT-PCR) assay results. We found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…Nie et al evaluated the Alere i system with the FilmArray respiratory panel (RP) (BioFire Diagnostics, Salt Lake City, UT) using frozen NP swabs in viral transport media, using the Prodesse ProFluϩ assay (Gen-Probe, San Diego, CA) for discrepant analysis (9). Bell and Selvarangan reported similar findings comparing the results of Alere i system to those of viral culture, with discrepant analysis by the Prodesse ProFluϩ assay in their pediatric study (10). Validating performance parameters with UTM means continued use of a common collection system currently in place in our laboratory and the availability of additional specimens without having to collect additional samples for subsequent testing, which may be necessary to clarify respiratory diagnoses, such as coinfections, or address specific infection control requirements (1, 2, 11).…”
supporting
confidence: 64%
“…Nie et al evaluated the Alere i system with the FilmArray respiratory panel (RP) (BioFire Diagnostics, Salt Lake City, UT) using frozen NP swabs in viral transport media, using the Prodesse ProFluϩ assay (Gen-Probe, San Diego, CA) for discrepant analysis (9). Bell and Selvarangan reported similar findings comparing the results of Alere i system to those of viral culture, with discrepant analysis by the Prodesse ProFluϩ assay in their pediatric study (10). Validating performance parameters with UTM means continued use of a common collection system currently in place in our laboratory and the availability of additional specimens without having to collect additional samples for subsequent testing, which may be necessary to clarify respiratory diagnoses, such as coinfections, or address specific infection control requirements (1, 2, 11).…”
supporting
confidence: 64%
“…The present study evaluated the performance of Alere iNAT against existing RIDTs using RT‐PCR as the reference standard for the detection of influenza viruses on clinical specimens collected from patients with an ILI. Others have previously compared Alere iNAT against RT‐PCR and/or viral culture using prospectively collected or frozen samples . Overall, Alere iNAT has demonstrated superior performance to the other RIDTs, particularly in the detection of influenza B.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of paediatric samples may have also lowered the observed sensitivity of all RIDTs tested; previous meta‐analyses have suggested improved RIDT sensitivity of up to 13% in children as they generally have higher viral loads and prolonged viral shedding compared to adults . A recent study of Alere iNAT performance in children and adolescents reported sensitivities and specificities of 88·8% and 98·3%, respectively, for influenza A and 100% and 100%, respectively, for influenza B compared to RT‐PCR …”
Section: Discussionmentioning
confidence: 99%
“…an independent conclusion about the assay performance. Other studies report a sensitivity of Alere TM Influenza A&B of 73%-99% for influenza-A, 97%-100% for influenza-B; and specificity of 95%-100% for influenza-A, and 100% for influenza-B [9][10][11].…”
Section: The Overall Low Number Of Influenza-b In Both Test Series LImentioning
confidence: 97%